Taxes and New Product Development: An Operational Management Perspective - Muhammad Yamin Noch; Mohammad Ridwan Rumasukun (Golden Ratio of Taxation Studies, 2023)
This study explores the intricate relationship between taxation policies and new product development (NPD) from an operational management perspective. The primary objective is to comprehensively analyze and interpret existing scholarly works to develop a nuanced understanding of how taxes influence firms' innovation behavior and performance throughout the NPD lifecycle. A qualitative research methodology is employed, involving defining the research scope, identifying relevant literature, data collection, analysis, and interpretation. Through a systematic literature review, key insights are synthesized, revealing the significant impact of tax incentives on firms' innovation activities. The findings highlight the role of tax incentives in stimulating R&D investments, fostering innovation, and enhancing firms' competitiveness in the marketplace. The study also identifies challenges such as regulatory uncertainties and global tax competition, which firms must navigate to effectively leverage tax incentives and drive sustainable growth. Overall, the research contributes to advancing theoretical understanding and managerial practice by shedding light on the complex relationship between taxes and NPD, offering valuable insights for policymakers, practitioners, and researchers alike.